2018
DOI: 10.1177/0892705718796544
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical investigations of SiC and Al2O3–reinforced HDPE

Abstract: This research work highlights the thermomechanical investigations of silicon carbide (SiC) and aluminum oxide (Al2O3)–reinforced high-density polyethylene (HDPE)–based feed stock filament of commercial fused deposition modeling (FDM) setup. The recycled HDPE waste was collected (from domestic waste) and washed with water jet for removal of contamination in the first stage. After contamination removal, rheological and thermal behavior (melt flow index, melting temperature, decomposition and enthalpy, etc.) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The literature reveals that the use of biodegradable/green waste enhances the mechanical properties and reduces the environmental pollution as well as cost [25][26][27][28][29][30][31]. But hitherto little has been reported on the use of the almond skin in powder form for enhancement of the compressive properties [13,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals that the use of biodegradable/green waste enhances the mechanical properties and reduces the environmental pollution as well as cost [25][26][27][28][29][30][31]. But hitherto little has been reported on the use of the almond skin in powder form for enhancement of the compressive properties [13,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with the observations made by other investigators. 29,[31][32][33] The reason for composition/proportion F: 90% ABS-10% B-0% Al 2 O 3 -0% SiC is but obvious because absence of ceramics in the composite matrix is supposed to improve tensile properties. The highest temperature condition 230 C with lowest 30 r min À1 and 5 kg feeding load is also but obvious settings as these settings will result into better flowability of composite material resulting into more uniform dispersion which has been observed in photomicrographs (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26] The published literature highlights that the recycling of ABS or other thermoplastics by primary/secondary/tertiary/quaternary methods is being done in isolation. [27][28][29] But while dealing with the plastic solid waste (in bulk), it is practically difficult to distinguish between the thermoplastic and the thermosetting waste. So an intermediate route/technique is required to process the plastic solid waste comprising of both the thermoplastic and thermosetting materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the mechanical properties of the composite laminates were found to have improved to a large extent when compared to the usual standard HDPE laminates. New solutions to improve the mechanical properties of the HDPE are presented in [11][12][13][14][15].The finite element method is usually used to determine the strange-stress field in the HDPE pipes. The visco-elastic constitutive model with Prony series was carried out to obtain a temperature field and the stress-stress field in the welding stages [16].…”
mentioning
confidence: 99%
“…It is observed that the mechanical properties of the composite laminates were found to have improved to a large extent when compared to the usual standard HDPE laminates. New solutions to improve the mechanical properties of the HDPE are presented in [11][12][13][14][15].…”
mentioning
confidence: 99%